비점오염 관리평가를 위한 부하지속곡선 작성시 모니터링 자료 활용 방안 - 박현규; 정민혁; 범진아; 최동호; 정재운; 고재한; 김영석; 윤광식 (한국수처리학회지, 27(4), 2019)
The ministry of environment (MOE) in korea recommends application of the flow duration curve (FDC) and load duration curve (LDC) using past 10 years flow rate to manage the total pollutant. However, the new management site has difficulties for assessment of the total pollution due to the lack of 10 year flow rate data. In this study, we compare the result of FDC using past 3 years data, 5 years data and 10 years data in Pungyeongjeongcheon watershed. We monitored the water quality of both rainfall event and dry event and compared to the 8 days data which were monitored by MOE. The water quality showed that observed dry event data and 8 days data shows similar concentration. But, rainfall event data shows higher concentration than 8 days data by MOE. Moreover, the result of LDC using both monitored data and 8 days data shows higher excess rate in the high flow conditions, and it shows 30 % higher excess rate above target goal than LDC using only 8 days data. Based on this results, the estimation of excess rate using additional monitoring data in rainfall event can be made more reliable result to manage the nonpoint source pollutant with LDC method. KCI Citation Count: 0